From the Constitutional Abolitionism to the Abolition of the Constitution: Lysander Spooner on Freedom, Slavery and the Limits of the Social Compact - Gogłoza, Włodzimierz (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
Lysander Spooner (1808-1887) – a self-taught lawyer whose opinions have been quoted by the Supreme Court of the United States, a private entrepreneur challenging government monopolies, and a doyen of American individualism, is currently known mainly as a trenchant critic of the United States Constitution, who openly contested its legitimacy. His early abolitionist works, in which he argued that slavery was illegal under the Constitution, are far less known but equally thought-provoking and important. The aim of this paper is to analyze the evolution of Spooner’s political stance from the most influential exponent of the antislavery constitutionalism to an anarchist who demanded the abolition of constitution, as well as to mark out the limits he tried to put on the social compact.